Prospek dan Tantangan Pendidikan Inklusi di Indonesia dalam Mewujudkan Sustainable Development Goals (SDGs) 2030 - Dede Sri Martini; Silvia Sri Wulandari; Ichsan Fauzi Rachman (Politeknik Kampar, 2025)
Inclusive education has a very important role in supporting the achievement of the 2030 Sustainable Development Goals (SDGs) in Indonesia. This research aims to analyze the prospects and challenges of inclusive education in Indonesia. This research uses the literature study method, by analyzing data from various sources related to the prospects and challenges of inclusive education in Indonesia. The results show that some positive prospects are seen in the increasing public awareness and government policies that increasingly support inclusive education. Nevertheless, several obstacles must be addressed, including a shortage of qualified teachers, inadequate educational facilities and infrastructure, as well as ongoing social resistance to the concept of inclusivity. Addressing these issues requires strong collaboration between stakeholders and the adoption of innovative implementation strategies. This study concludes that inclusive education is vital for fostering a more fair and equal educational system.